The new NHS: an ethnographic case study of the role of professionals in policy reform - Clegg Smith, Katherine (2002)
The National Health Service (NHS) holds an esteemed position within Britain's `welfare state'. Since its inception, however, it has been subject to near constant reforms, seemingly intended to balance public expectations with available resources. Successive governments have required professional collaboration to gain crucial popular support, and increasingly, general practitioners have been prioritised within reform initiatives.